2015
DOI: 10.2139/ssrn.2595576
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal and Economic Aspects of Book Consumption in the European Union

Abstract: One of the available and yet controversial tools in cultural policy at the national level is the reduction of VAT rates for cultural goods and services. We document the standard and reduced VAT rates in EU-28 countries in the period from 1993 to 2013 and explore the underlying determinants. We further introduce a simple theoretical framework to explain how reduced fiscal rates are expected to decrease prices and increase quantities of the consumed cultural goods and services. We then estimate quantitatively th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…3. On the issue of funding heritage institutions, and cultural consumption more in general, refer to Borowiecki and Navarrete (2015). 4.…”
Section: Discussionmentioning
confidence: 99%
“…3. On the issue of funding heritage institutions, and cultural consumption more in general, refer to Borowiecki and Navarrete (2015). 4.…”
Section: Discussionmentioning
confidence: 99%
“…There, the decrease of the applicable VAT rate from 19% to just 10% was not enough to drive demand, possibly because of the low levels of overall household income. This contradicts a cross-country EU study, which found that, usually, low VAT rates on books equal lower prices and drive consumption of these goods up, reaffirming the rationale behind their inclusion in the reduced rates' regime (Borowiecki and Navarrete, 2015).…”
Section: Positive Externalitiesmentioning
confidence: 62%
“…According to de la 2015). Setting reduced rates on these correlates with the theory that the market cannot internalise their externalities, thus impeding their effective circulation and allocation (Borowiecki and Navarrete, 2015). This is precisely the reason why states intervene through their fiscal policies, including VAT planning, to try and tackle such complications.…”
Section: Positive Externalitiesmentioning
confidence: 99%
See 2 more Smart Citations